Ethical Implementation and Responsible Utilization of Technology in English Language Learning - Reftyawati, Dian (STKIP PGRI Bandar Lampung, 2024)
This study investigates the implementation of ethics and responsibility in utilizing technology for English language learning within senior high school classrooms. Employing a qualitative research design, the study utilizes descriptive and qualitative approaches to analyze data, facilitating comprehension and drawing conclusions. Thematic structure analysis is employed to interpret the data, collected through semi-structured interviews. Findings suggest that English teachers in senior high schools adhere to ethical and responsible guidelines in technology usage. This research contributes insights into the ethical considerations and responsible practices associated with integrating technology into English language learning within senior high school settings.